Implementation of Extracurricular Management in Optimizing the Non-Academic Potential of Elementary School Students - Afriska Hernaning Tiyas; Erny Roesminingsih; Mohammad Syahidul Haq (Poltanesa, 2025)
Optimizing the non-academic potential of elementary school students is an important aspect that deserves attention in the field of education, in line with efforts to develop human resources toward Indonesia Emas 2045. Through extracurricular activities, schools provide opportunities for students to express and develop their potential, particularly in non-academic areas. This study aims to examine the implementation of extracurricular activity management in efforts to optimize the non-academic potential of elementary school students. The research uses a qualitative approach with a multi-site case study design conducted at SDN Kauman 1 and SDN Ngrowo 2 Bojonegoro District. Data collection techniques include in-depth interviews, observation, and document analysis. Data analysis in this study employs the Miles and Huberman model, which involves two stages: single-site data analysis and cross-site analysis. The study results demonstrate that proper managerial practices and the systematic application of the four management functions—planning, organizing, implementation, and evaluation yield significant success in developing and optimizing elementary students' non-academic potential.